Enzalutamide in Japanese patients with chemotherapy‐naïve, metastatic castration‐resistant prostate cancer: A post‐hoc analysis of the placebo‐controlled PREVAIL trial. (27th March 2016) - Kimura, Go; Yonese, Junji; Fukagai, Takashi; Kamba, Tomomi; Nishimura, Kazuo; Nozawa, Masahiro; Mansbach, Hank; Theeuwes, Ad; Beer, Tomasz M; Tombal, Bertrand; Ueda, Takeshi
Abstract : Objectives: To evaluate the treatment effects, safety and pharmacokinetics of enzalutamide in Japanese patients. Methods: This was a post‐hoc analysis of the phase 3, double‐blind, placebo‐controlled PREVAIL trial. Asymptomatic or mildly symptomatic chemotherapy‐naïve patients with metastatic castration‐resistant prostate cancer progressing on androgen deprivation therapy were randomized one‐to‐one to 160 mg/day oral enzalutamide or placebo until discontinuation on radiographic progression or skeletal‐related event and initiation of subsequent antineoplastic therapy. Coprimary end‐points were centrally assessed radiographic progression‐free survival and overall survival. Secondary end‐points were investigator‐assessed radiographic progression‐free survival, time to initiation of chemotherapy, time to prostate‐specific antigen progression, prostate‐specific antigen response (≥50% decline) and time to skeletal‐related event. Results: Of 1717 patients, 61 were enrolled in Japan (enzalutamide, n = 28; placebo, n = 33); hazard ratios (95% confidence interval) of 0.30 for centrally assessed radiographic progression‐free survival (0.03–2.95), 0.59 for overall survival (0.20–1.8), 0.46 for time to chemotherapy (0.22–0.96) and 0.36 for time to prostate‐specific antigen progression (0.17–0.75) showed the treatment benefit of enzalutamide over the placebo. Prostate‐specific antigen responses were observed in 60.7% of enzalutamide‐treated men versus 21.2% of placebo‐treated men. Plasma concentrations of enzalutamide were higher in Japanese patients: the geometric mean ratio of Japanese/non‐Japanese patients was 1.126 (90% confidence interval 1.018–1.245) at 13 weeks. Treatment‐related adverse events grade ≥3 occurred in 3.6% of enzalutamide‐ and 6.1% of placebo‐treated Japanese patients. Conclusion: Treatment effects and safety in Japanese patients were generally consistent with the overall results from PREVAIL.